你可能感兴趣的试题
={x|﹣1<x<2}, ={x|x2+2x≤0},则A.∩B.=( ) A.{x|0<x<2}B.{x|0≤x<2} {x|﹣1<x<0} {x|﹣1<x≤0}
={x|x2﹣2x﹣3<0}, ={x||x|<2}则A.∩B.=( ) A.{x|﹣2<x<2}B.{x|﹣2<x<3} {x|﹣1<x<3} {x|﹣1<x<2}
={x|(1-x)·(x+2)≤0},则∁R.A.=( ) A.{x|x<-2,或x>1} {x|x≤-2,或x≥1} {x|-2{x|-2≤x≤1}
={x|x>1}, ={x|x2﹣2x<0},则A.∪B=( ) A.{x|x>0}B.{x|x>1} {x|1<x<2} {x|0<x<2}
f(x)=x2+2x+1 f(x)=x2﹣2x+1 f(x)=x2+2x﹣1 f(x)=x2﹣2x﹣1
={x|x>1}, ={x|-1-1} {x|-1{x|1
f(x)=x2+1 f(x)=x2+2x-1 f(x)=x2-1 f(x)=x2+2x+1
={x|1<x≤3}, ={x|x>2},则A.∩B等于( ) A.{x|1<x≤2}B.{x|1≤x≤2} {x|1≤x≤3} {x|2<x≤3}
f(x﹣1)=2x+2(0≤x≤2) f(x﹣1)=﹣2x+1(2≤x≤4) f(x﹣1)=2x﹣2(0≤x≤2) f(x﹣1)=2x﹣1(2≤x≤4)
f(x-1)=2x+2(0≤x≤2) f(x-1)=2x-1(2≤x≤4) f(x-1)=2x-2(0≤x≤2) f(x-1)=-2x+1(2≤x≤4)
{x|﹣3<x<2} {x|﹣3<x<1} {x|1<x<2} {x|2<x<3}